2005
DOI: 10.1111/j.1440-1789.2005.00596.x
|View full text |Cite
|
Sign up to set email alerts
|

Degeneration of the inferior olive in spinocerebellar ataxia 6 may depend on disease duration: Report of two autopsy cases and statistical analysis of autopsy cases reported to date

Abstract: This report concerns a clinicopathological study of two autopsied patients with spinocerebellar ataxia 6 (SCA6), and a statistical analysis between neuronal loss of the inferior olive and disease duration of 15 SCA6 autopsy cases reported to date, including the two cases reported in this study. Cases 1 and 2 came from independent Japanese families. Case 1 developed gait disturbance at age 35 years and died at age 78 years; she had a CAG-repeat expansion of the SCA6 gene (25/13). Case 2 presented with gait dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
11
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 38 publications
(59 reference statements)
3
11
0
Order By: Relevance
“…In contrast, in case 3, which did not show distinct neuronal loss in the inferior olivary nucleus, the duration of illness was shorter than in other cases, the granular cell loss and narrowing of the molecular layer was mild and there were few lesions belonging to Grade 3 or more. These findings suggest that the lesion of the inferior olivary nucleus is related to the level of cerebellar cortical lesion, especially changes of the granular cell and molecular layer and to the period of suffering from the disease as well as SCA6 18 . As mentioned above, our study disclosed that cerebello‐olivary degeneration of idiopathic LCCA has a striking resemblance to that of SCA6 13–16 .…”
Section: Discussionsupporting
confidence: 72%
“…In contrast, in case 3, which did not show distinct neuronal loss in the inferior olivary nucleus, the duration of illness was shorter than in other cases, the granular cell loss and narrowing of the molecular layer was mild and there were few lesions belonging to Grade 3 or more. These findings suggest that the lesion of the inferior olivary nucleus is related to the level of cerebellar cortical lesion, especially changes of the granular cell and molecular layer and to the period of suffering from the disease as well as SCA6 18 . As mentioned above, our study disclosed that cerebello‐olivary degeneration of idiopathic LCCA has a striking resemblance to that of SCA6 13–16 .…”
Section: Discussionsupporting
confidence: 72%
“…A neuropathological examination by Gomez and colleagues12 showed that the substantia nigra and striatum had no significant cell loss. Tsuchiya and colleagues13 also reported that neuronal loss was not evident in these areas, and post-mortem studies by Takahashi and colleagues14 and Tashiro and colleagues15 produced similar findings. Furthermore, dopamine transporter (DAT) positron emission tomography using [ 11 C]d-threo-methylphenidate revealed that SCA6 has normal binding potential16 but Khan and colleagues,10 using [ 18 F]-dopa positron emission tomography, reported that the nigrostriatal dopaminergic system is involved in SCA6.…”
Section: Introductionmentioning
confidence: 74%
“…Tsuchiya et al. stated that in SCA 6, degeneration of the inferior olivary nucleus depends on disease duration 16 . The clinical disease duration in the case of Owada et al.…”
Section: Discussionmentioning
confidence: 99%